House Dust Mite Species in Ordu, Turkey - Rana Akyazı; Mete Soysal; Pavel B. Klimov; Yunus Emre Altunç (Journal of Agricultural Sciences)
House dust mites inhabit human houses, causing allergies and respiratory disease. Of them pyroglyphid mites produce at least 23 allergen groups, affecting millions of people worldwide. We determined the house dust mite fauna in the city of Ordu situated on the Black Sea coast of Turkey. Dust samples were taken from a total of 53 houses in 2013-2015. The mite family Pyroglyphidae had the highest abundance in our samples, followed by family Chortoglyphidae. The most common species were Dermatophagoides pteronyssinus (Trouessart) and Dermatophagoides farinae Hughes (Astigmata: Pyroglyphidae). These two mite species are main allergen-producing species throughout the world, occurring in all sampled houses in the city of Ordu.